Decision ecology: what natural decision-making tells us about the structure of the brain and neural systems - Stephens, David W. (Henry Stewart Talks, 2017)
The patch exploitation problem animal face, Choice in the laboratory: self-control and impulsivity, Ecological rationality, Evolutionary mismatch, Decoy effect and the independence of irrelevant options, The importance of comparative preference